2021
DOI: 10.21203/rs.3.rs-677461/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Trends and Treatment Outcomes of Pediatric Tuberculosis at Mbale Regional Referral Hospital, in Eastern  Uganda, 2013-2017

Abstract: Background: Childhood tuberculosis (TB) remains a major public health problem in Uganda. Failure to complete TB treatment is associated with development of multi-drug-resistant TB, continued spread of TB, and death. The World Health Organization (WHO) recommends treatment success rates of ≥85% to achieve TB control, but children often have lower success rates due to challenges in case identification and treatment adherence. We assessed trends in childhood TB case notification rates, spatial case distribution, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Childhood tuberculosis represented 352 (47%) of all registered cases in Moroto district. Similar high case numbers were reported by (5,20) in Mbarara and Mbale districts respectively, however (6) reported a lower TB frequency of 7.5% in Kampala. Other developing countries such as Pakistan reported high case numbers at 42.4% while Kenya reported low frequency at 9% ( 21).…”
Section: A) Childhood Tuberculosis Reported At Health Facilities and ...supporting
confidence: 76%
See 2 more Smart Citations
“…Childhood tuberculosis represented 352 (47%) of all registered cases in Moroto district. Similar high case numbers were reported by (5,20) in Mbarara and Mbale districts respectively, however (6) reported a lower TB frequency of 7.5% in Kampala. Other developing countries such as Pakistan reported high case numbers at 42.4% while Kenya reported low frequency at 9% ( 21).…”
Section: A) Childhood Tuberculosis Reported At Health Facilities and ...supporting
confidence: 76%
“…This could explain why the completion rates are below 100%. Previous studies in Uganda by (20,25) reported lower completion rates in rural areas at 29% for Butaleja and 48% for Mbale respectively. This increase in completion rate should be attributed to current efforts by Ministry of Health of Uganda and her partners that has put deliberate efforts in improving the coverage treatment coverage in Teso and Karamoja region (Nidoi et al, 2021).…”
Section: A) Childhood Tuberculosis Reported At Health Facilities and ...mentioning
confidence: 85%
See 1 more Smart Citation